In vivo Evaluation of Nanostructured Fibrin-Agarose Hydrogels With Mesenchymal Stem Cells for Peripheral Nerve Repair - Chato-Astrain, Jesús; Campos, Fernando; Roda, Olga; Miralles, Esther; Durand-Herrera, Daniel; Sáez-Moreno, José Antonio; García-García, Salomé; Alaminos, Miguel; Campos, Antonio; Carriel, Víctor (Frontiers in Cellular Neuroscience, 2018)
The regenerative capability of peripheral nerves is very limited, and several strategies have been proposed to increase nerve regeneration. In the present work, we have analyzed the in vivo usefulness of a novel nanostructured fibrin-agarose bio-artificial nerve substitute (Nano) used alone or in combination with NeuraGen® collagen type I conduits (Coll-Nano) in laboratory rats with a 10-mm sciatic nerve defect. Control animals were subjected to the gold-standard autograft technique (Auto). Results first demonstrated that the percentage of self-amputations was lower in Nano and Coll-Nano groups as compared to the Auto group. Neurotrophic ulcers were more abundant in the Auto group (60%, with 66.6% of them being >2-mm) than Nano and Coll-Nano groups (0%) at 4 weeks, although Nano showed more ulcers after 12 weeks. Foot length was significantly altered in Auto animals due to neurogenic retraction, but not in Nano and Coll-Nano groups after 12 weeks. At the functional level, all animals showed a partial sensory recovery as determined by the pinch test, especially in Nano and Auto groups, but did not reach the levels of native animals. Toe-spread test revealed a partial motor function recovery only in Nano animals at 4 weeks and Auto and Nano at 12 weeks. Electromyography showed clear denervation signs in all experimental groups, with few differences between Auto and Nano animals. After 12 weeks, an important denervation decrease and an increase of the reinnervation process was found in Auto and Nano groups, with no differences between these groups. Histological analyses demonstrated an active peripheral nerve regeneration process with newly formed peripheral nerve fascicles showing S-100, GAP-43 and myelin in all experimental groups. The peripheral nerve regeneration process was more abundant in Auto group, followed by Nano group, and both were better than Coll-Nano group. Muscle histology confirmed the electromyography results and showed some atrophy and fibrosis signs and an important weight and volume loss in all groups, especially in the Coll-Nano group (56.8% weight and 60.4% volume loss). All these results suggest that the novel Nano substitutes used in in vivo were able to contribute to bridge a 10-mm peripheral nerve defect in rats.